Influence Impact of Sustainability Report Disclosure on Stock Prices - Nur Frila Mirdayanti; NA Rumiasih; Yudiana Yudiana; Ofan Maulana Yudista (Program Studi Akuntansi Universitas Ibn Khaldun Bogor, 2026)
This study aims to analyze the effect of sustainability report disclosure on stock price in banking subsector companies listed on the Indonesia Stock Exchange (IDX) for the 2020-2024 period. The independent variables include sustainability report disclosure of economic, social, environmental aspects, while the dependent variable is stock price. This study employed a quantitative method with secondry data obtained from sustainability reports and company stock price data. Using a purposive sampling technique, 28 companies were selected with a total of 140 observatons . After removing outliers, 90 data were used in the analysis. This study utilized SPSS software and multiple linear regression analysis. The results showed that, simultaneously, sustainability report disclosure significantly affected stock prices. Partially, economic disruption had no significant effect on stock prices. environmental disclosure had a negative but significant effect on stock prices, and social disclosure had a positive and significant effect on stock prices.